2003
DOI: 10.1097/00126334-200304010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Placenta and Cord Blood Mitochondrial DNA Toxicity in HIV-Infected Women Receiving Nucleoside Reverse Transcriptase Inhibitors During Pregnancy

Abstract: Recent studies of pregnant women and animal models have raised concerns regarding potentially serious mitochondrial toxicity-related side effects in infants born to mothers who received nucleoside reverse transcriptase inhibitors (NRTIs) during their pregnancy to prevent HIV-1 perinatal transmission. The aim of this study was to assess mitochondrial DNA (mtDNA) content of cord blood and placenta in HIV-infected pregnant women receiving NRTI compared with HIV-negative women, hypothesizing that placenta and cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 20 publications
4
62
2
Order By: Relevance
“…2,3 Recent studies have found significantly higher mtDNA levels in peripheral blood mononuclear cells (PBMCs) of HIV-uninfected infants exposed to NA and to other ARV compared to ARV-unexposed infants at birth and in the first few weeks of life, [4][5][6] possibly to due compensatory mitochondrial activity in response to NA-induced stress. These findings contradict earlier studies, which reported decreased mtDNA in cord blood and PBMCs in ARVexposed infants at birth and at 1 and 2 years of age, [7][8][9] and a recent study that found mtDNA depletion with secondary respiratory chain compromise in placental tissue with ARV exposure. 10 Other findings include significantly lower mitochondrial RNA (mtRNA) levels at birth in NA-exposed vs. unexposed infants 4 and no difference in cytochrome c oxidase protein levels.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2,3 Recent studies have found significantly higher mtDNA levels in peripheral blood mononuclear cells (PBMCs) of HIV-uninfected infants exposed to NA and to other ARV compared to ARV-unexposed infants at birth and in the first few weeks of life, [4][5][6] possibly to due compensatory mitochondrial activity in response to NA-induced stress. These findings contradict earlier studies, which reported decreased mtDNA in cord blood and PBMCs in ARVexposed infants at birth and at 1 and 2 years of age, [7][8][9] and a recent study that found mtDNA depletion with secondary respiratory chain compromise in placental tissue with ARV exposure. 10 Other findings include significantly lower mitochondrial RNA (mtRNA) levels at birth in NA-exposed vs. unexposed infants 4 and no difference in cytochrome c oxidase protein levels.…”
Section: Introductioncontrasting
confidence: 99%
“…Standardization of real-time PCR was performed using LightCycler FastStart DNA Master SYBR Green I with the Roche LightCycler instrument (Roche, Indianapolis, IN). A dilution series of the control plasmid 7 containing the 90-bp mtDNA NADH dehydrogenase, subunit 2 and the 98 bp Fas Ligand gene was prepared to set up the standard. Each sample and standard was run in duplicate and the results were analyzed with Version 4.0 LightCycler software.…”
Section: Mtdna Copies/cell Quantitationmentioning
confidence: 99%
“…9 Only a few studies have analyzed mtDNA copy numbers in infants perinatally exposed to ARVs and reported conflicting data. Although some of these studies have documented mtDNA depletion in peripheral blood mononuclear cells (PBMCs), [10][11][12] others have shown no change 8,13 or even increased mtDNA copy numbers compared to infants not exposed to HIV or NRTI therapy. 14,15 A small study has analyzed the mitochondrial ultrastructure by electron microscopy and has identified significant damage of the organelles in six out of nine NRTI-exposed infants compared to none of seven infants born to HIV-negative women.…”
mentioning
confidence: 99%
“…Intact DNA was assayed for mitochondrial DNA (mtDNA) copies per cell using mt primers that amplify a region of mtDNA (90 bp) that encodes for NADH dehydrogenase subunit 2 and genomic primers specific for the region of the genome encoding the Fas ligand (98 bp) by real-time PCR. 30 The PCR reactions were assayed with the Lightcycler FastStart DNA Master SYBR Green I mix in the LightCycler real-time instrument (Roche Diagnostic Corporation, Indianapolis, IN). Each sample and standard was run in duplicate (20 L reaction volume) containing 1X SYBR Green master mix, 0.5 M of each primer, and a 10 ng sample of DNA.…”
mentioning
confidence: 99%
“…Mitochondrial DNA copies per cell were calculated using the formula (mtDNA copies/genomic DNA copies) ϫ 2 ϭ mtDNA copies per cell. 30 Definitions of DSP. TNS.…”
mentioning
confidence: 99%